The philosophical foundations of music education – old and new - Tóth, Rita Zsófia (Acta Cultura et Paedagogicae, 2026)
Music education may seem to be a matter of mere pedagogical practice at first glance, but in many essential respects, it also involves philosophical questions. Questions such as: is music something discovered or something created? Why do people make music, and why do they feel compelled to do so? What makes a musical work good? What is the role of music in society, and what is its place in education? Do children learn musical works intellectually, through thinking, or motor and mechanical exercises? Or both at the same time? And how? In the natural and social sciences, knowledge can be assessed throughout education through written and oral examinations and tests, but in the case of music, how can a child's understanding of works of art and general musical knowledge be assessed if it is not just lexical knowledge? What is musical knowledge? What is musical talent, which can be defined as a natural ability or skill in music? How many talents and skills constitute musical talent? My lecture is part of my doctoral thesis. It deals with the philosophical aspects of music education, tracing its roots back to antiquity. Philosophical writings generally reflect on the purpose, meaning, value, and impact of music education on human development and society. As Dewey (1916) suggests, philosophy can be seen as a general theory of education. In my lecture, I would like to provide a general understanding of the philosophical questions, both ancient and contemporary, about music education and attempt to answer them. This theoretical inquiry aims to contribute to the development of a new philosophy of music education, which I believe will foster innovative trends and ideas in related disciplines by offering a more comprehensive and nuanced understanding of music education. I hope that this new philosophy will inspire and guide future developments in music education.